First insight into divergence, representation and chromosome distribution of reverse transcriptase fragments from L1 retrotransposons in peanut and wild relative species - Samoluk, Sergio Sebastián (2015)
Peanut is an allotetraploid (2n = 2x = 40, AABB) of recent origin. Arachis duranensis and A. ipaënsis, the most probable diploid ancestors of the cultigen, and several other wild diploid species with different genomes (A, B, D, F and K) are used in peanut breeding programs. However, the genomic relationships and the evolutionary pathways of genome differentiation of these species are poorly understood. We performed a sequence-based phylogenetic analysis of the L1 reverse transcriptase and estimated its representation and chromosome distribution in species of five genomes and three karyotype groups with the aim of contributing to the knowledge of the genomic structure and evolution of peanut and wild diploid relatives. All the isolated rt fragments were found to belong to plant L1 lineage and were named ALI. The best supported phylogenetic groups were not concordant with the genomes or karyotype groups. The copy number of ALI sequences was higher than the expected one for plants and directly related to genome size. FISH experiments revealed that ALI is mainly located on the euchromatin of interstitial and distal regions of most chromosome arms. Divergence of ALI sequences would have occurred before the differentiation of the genomes and karyotype groups of Arachis. The representation and chromosome distribution of ALI in peanut was almost additive of those of the parental species suggesting that the spontaneous hybridization of the two parental species of peanut followed by chromosome doubling would not have induced a significant burst of ALI transposition.